The COVID-19 Pandemic and the Peruvian Catholic Church: : A New Stage in Its Reception of Vatican II? - Juan Miguel Espinoza Portocarrero (Lumen et Vita, 2020)
This paper examines the Peruvian Catholic Church's responses to the challenges of COVID-19, and how this context might constitute a new stage of the Peruvian Church’s reception of Vatican II. First, it values that the Catholic Church has performed a significant social contribution by distributing humanitarian aid, providing spiritual accompaniment, and articulating the civil society to face the needs raised by COVID-19. This paper argues that such response relates to the process of reception of Vatican II in Peru. During the 1970s and 1980s, the Peruvian Church developed pastoral structures and ecclesial networks that specialized in engaging with and serving the world. Nowadays, the Church offers those strengths to the State and society. Second, this paper examines how the pandemic presents opportunities for a new discernment of the "signs of the times" by highlighting some pastoral challenges the Peruvian Church needs to address in light of Peru’s new social reality and Pope Francis’ call for Church reform.